PERLINDUNGAN HUKUM TERHADAP MASYARAKAT YANG TELAH DIVAKSIN COVID 19 DAN MEMPUNYAI EFEK BAGI KESEHATANNYA - Rastra Samudera Perdana (Fakultas Ilmu Sosial dan Humaniora, 2023)
The background of writing a vaccine that effects occurring in those whose above 60 years and them with the ( ko-morbid ) companion , that have high risk for contracting , a heavy and vulnerable to disease risk death .The data suggested that those aged over 65 was % 9 of the world population , but on the other side 30 % - % covid - 19 40 cases are those in the world who are over 65 years and also about 80 % deaths resulting from the disease .The high risk to be covered , because it will bring a lot of influence in the pain and even death .Cases have occurred in the indonesia in relation effect on administering vaccine for recipients vaccine what happens like the example occurred in the town of semarang , 95 people within the city of semarang virus infected corona after undergoing vaccination .There were 160 confirmation is vaccination positive after the first , and there are 35 confirmation is vaccination positive after the second. Is the case with cities manado , astrazeneca vaccine been suspended after residents feel the impact of the as a fever , shivering , headache , the hurt and limp .Cases have occurred in the city of banyumas , 2 the elderly died after the vaccine